Positive Predictive Value of Transvaginal Doppler Ultrasound in The Diagnosis of Endometrial Polyp Taking Histopathology as Gold Standard - Zaka, Amina; Hayat, Abdul Malik; Nizam, Mehwish; Ashraf, Aasma; Fatima, Saba; Ahmad, Tanweer (British Journal of Healthcare and Medical Research, 2023)
Background: Endometrial or uterine polyps are masses arising from the mucosal layer of the uterine endometrium. No definitive cause of endometrial polyps is known, but they are likely affected by hormone levels and grow in response to circulating estrogen. Endometrial polyps are usually benign, however some ca be precancerous or cancerous. Objective: To evaluate the positive predictive value of transvaginal Doppler ultrasound in the diagnosis of endometrial polyps taking histopathology as the gold standard. Material & Methods: Study Design: Cross sectional study. Setting: Department of Diagnostic Radiology, Sir Ganga Ram Hospital, Lahore. Duration: 3 months i.e. 01-02-2023 to 30-04- 2023. Data collection: 165 patients were enrolled. The mean age of patients was 38.93±6.85 years. Transvaginal sonography was performed for all patients. After the receipt of histopathology results from the laboratory, final diagnosis was made and values for determining the PPV of TVS in diagnosis of endometrial polyp were calculated. Results: The PPV of TVS was 88.64% with histopathology as the gold standard. Conclusion: The transvaginal Doppler USG is a reliable and useful tool in the diagnosis of endometrial polyp taking histopathology as gold standard and have high value of PPV.